Heat Stress and Body Temperature in Brown Swiss Cows Raised in Semi-Arid Climate of Ceará State, Brazil - Leles, Jaqueline Silva; Rodrigues, Inti Campos Salles; Neto, Maurício Francisco Vieira; Neto, Aderson Martins Viana; Rocha, David Ramos da; Costa, Antônio Nelson Lima da; Salles, Maria Gorete Flores; Araújo, Airton Alencar de (Acta Scientiae Veterinariae, 2017)
Background: In tropical countries like Brazil, air temperature and relative humidity have a significant effect on animal physiology; there is a great impact of solar radiation on physiological parameters, especially on body temperature. This study evaluated the occurrence of heat stress in Brown Swiss cows in a tropical semi-arid climate, and checked for the correlation between internal body temperatures [rectal temperature (RT) and vaginal temperature (VT)] with surface temperature (ST) to determine if these variables are associated. Materials, Methods & Results: Twenty-eight Brown Swiss cows at three stages of the lactation cycle were used in this study: 10 nonpregant lactating (NPL) cows, 8 dry pregnant (DP) cows, and 10 pregnant lactating (PL) cows. These animals were between the second and third calving, weighed between 346 and 720 kg, and had ages between 2 and 13 years. During the experimental period, air temperature and relative humidity (RH) at the experimental site were measured using a digital thermohygrometer. The temperature and humidity index (THI) was calculated according to methodology described by Thom (1958), and was used as an environmental comfort parameter. For the evaluation of RT and VT, two digital clinical thermometers, one inserted in the vagina and the other in the rectum, were used simultaneously to minimize stress. Surface temperature (ST) was assessed using a digital infrared laser thermometer at a distance of 50 cm from the animal. Surface temperature was measured in the forehead (FST), thorax (TST), flank (FLST), and legs (LST). During the study period, the ambient temperature (AT) was significantly higher outside (in the sun) than inside of the facilities (in the shade) (P < 0.05). RH was inversely proportional to AT, and was significantly higher inside than outside the facilities (P < 0.05). Like AT, THI was significantly higher outside (in the sun) than inside the facilities (in the shade), with significant differences between these locations (P < 0.05). The amplitudes of the differences between the locations were as follows: 3.8°C for AT, 6.2% for RH, and 2.6 for THI. Mean values of rectal and vaginal temperatures were not significantly different from each other independent of lactation cycle stage, and were almost always significantly higher than the measured surface temperatures (P < 0.05). The maximum values obtained for each lactation cycle stage in this study were higher when compared to the mean values, showing that they are more representative of the occurrence of heat stress. Correlations between internal temperatures (RT and VT) and surface temperatures (TSF, TST, TSFL, and TSP) were weak and non-significant. ST values exhibited mostly weak, non-significant correlations, with the exception of FST with FLST and LST, which had moderate, significant correlations, as shown by the following coefficient factors: FST x FLST, 0.34; LST x FST, 0.415; and LST x FLST, 0.37. Discussion: A temperature of 34°C with RH ranging from 46% to 80% (i.e., a THI between 83 and 89) has been reported to have a significant thermal impact on dairy Brown Swiss cows; the THI values found in the present experiment were close to those. Body temperatures exhibited significant variations depending on the lactation cycle stage of the cows. Lactation concomitant with pregnancy significantly increases internal temperatures (RT and VT) in DP and NPL cows. This finding may be explained by the fact that pregnancy concomitant with lactation accelerates the metabolism, which results in higher food intake and increased production of body heat with consequent increase in internal body temperature. The maximum values of internal body temperatures (RT and TV) at all stages of the lactation cycle were higher than their corresponding average values, which indicates that some cows exhibited, at given moments, hyperthermia.